Fresno County Bar Association Law Day Luncheon: Judge Robert Coyle Speaker - Watkins, Howard::::::::: (1986)
Karen Yrulegui with Law League, Richard Yrulegui, Catherine Golden-Taylor, Mildred Christian with Legal Secretaries and Lee Cabibi with San Joaquin Association of Legal Assistants